A dipotassium 1, 2, 4-diazaphospholide dianion radical as an organometallic building block: the first 1, 2-diaza-4-phosphine ruthenocene. Issue 38 (12th September 2018) - Zhang, Xiang; Guo, Qiang; Zhang, Yuchen; Zhang, Yaona; Zheng, Wenjun
Abstract : A persistent dipotassium 1, 2, 4-diazaphospholide dianion radical (2 ) was used as a transfer agent for the preparation of a 1, 2-diaza-4-phosphine ruthenocene (4 ), which involved a reactive radical intermediate K + [(η 5 -CpMe5 Ru)(σ(P), σ(C)-(3, 5-Ph2 dp)˙] − (K + [5A ˙] − ). Abstract : A persistent dipotassium 3, 5-diphenyl-1, 2, 4-diazaphospholide dianion radical K + 2 [(3, 5-Ph2 dp)]˙ 2– (2 ) was synthesized and investigated by EPR analysis and magnetic susceptibility measurement, and it can be used as a transfer agent for the preparation of an unusual 1, 2-diaza-4-phosphine ruthenocene (4 ) with exclusive σ(P)-coordination. A plausible mechanism for the formation of4 was proposed as one that involves a reactive radical intermediate K + [(η 5 -CpMe5 Ru)(σ(P), σ(C)-(3, 5-Ph2 dp)˙] − ) (K + [5A ˙] − ) with σ(P)-coordination due to the high spin density (SD) at the phosphorus (σ 2 λ 3 ) atom.